2020
DOI: 10.1002/prp2.600
|View full text |Cite
|
Sign up to set email alerts
|

A simple open source bioinformatic methodology for initial exploration of GPCR ligands’ agonistic/antagonistic properties

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 47 publications
3
38
1
Order By: Relevance
“…Docking simulations of natural products, along with their analogs, from the ZINC database ( , accessed on 30 September 2021) [ 22 ] were performed on the 3CL-Pro crystal structure (pdb: 6YB7) as well as on key conformations out of the classical MD trajectories of the monomer produced by clustering in a fully flexible manner [ 23 ]. Fortunellin was identified as a key compound.…”
Section: Methodsmentioning
confidence: 99%
“…Docking simulations of natural products, along with their analogs, from the ZINC database ( , accessed on 30 September 2021) [ 22 ] were performed on the 3CL-Pro crystal structure (pdb: 6YB7) as well as on key conformations out of the classical MD trajectories of the monomer produced by clustering in a fully flexible manner [ 23 ]. Fortunellin was identified as a key compound.…”
Section: Methodsmentioning
confidence: 99%
“…This, as well as other changes, detailed in Figures S7 and S8 and Supplemental Table 1, results in a significant modification of transmembrane helices 3 and 4 (resulting in a significant reorientation of aminoacid residues in IL2) and helices 5 and 6, with a significant change in IL4 (Figure S8). These changes of IL2 and 3 are responsible for the decreased binding interaction of Gαi-GDP, as previously reported 3 .…”
Section: S3supporting
confidence: 85%
“…Our results (Figure S5) identified a binding pocket for 5-oxo-ETE and testosterone, proximal to the extracellular part of the receptor, similar to the one we have reported before 1 . Simulation binding of these two molecules 3 , after hydration of the receptor, reveals a number of common hydrogen or Van der Waals bond formation with Leu172, Ser173, Arg176, Leu227, Ser239, Tyr240, His253, Tyr257, Ser311 and Thr341, without or with the participation of water molecules. In addition, 5-oxo-ETE forms specific bonds with Val180 and Ile312, while testosterone (and B2-OPC) forms specific bonds with Thr231, Phe337, Ser340 and Leu341, suggesting that these latter amino acids might confer the antagonistic activity of testosterone (Supplemental Table 1).…”
Section: S3mentioning
confidence: 99%
“…Recently, we have shown that OXER1 can also be a membrane testosterone receptor , expressed in a number of cell lines and tissue specimens of prostate and breast cancer . Testosterone antagonized the effect of 5-oxo-ETE on the inhibition of cAMP production, through a hindering of G αi -GDP binding on the ligandreceptor complex (Panagiotopoulos et al, 2020). In addition, previous results of our group Panagiotopoulos et al, 2020) have shown that natural polyphenols (catechin, epicatechin and their natural dimers) interact with OXER1, eliciting antagonistic actions, similar to those of testosterone (in vitro and in vivo).…”
Section: Introductionmentioning
confidence: 73%
“…Testosterone antagonized the effect of 5-oxo-ETE on the inhibition of cAMP production, through a hindering of G αi -GDP binding on the ligandreceptor complex (Panagiotopoulos et al, 2020). In addition, previous results of our group Panagiotopoulos et al, 2020) have shown that natural polyphenols (catechin, epicatechin and their natural dimers) interact with OXER1, eliciting antagonistic actions, similar to those of testosterone (in vitro and in vivo). In this respect, these compounds could be good potential scafolds for the selection, design and development of novel OXER1antagonists.…”
Section: Introductionmentioning
confidence: 73%